Technology Adaptation in Mathematics Learning - Amelia Muhibatul Milah; Wati Susilawati; T. Tutut Widiastuti, A; Riva Lesta Ariany (Gunung Djati Conference Series, 2022)
The purpose of this research is to explain the role, principles and adaptation of technology integration in learning mathematics. The research method used is literature study based on literature and theoretical studies. The results of this study say that technology plays an important role in learning mathematics for more effective, creative, and innovative learning as well as being an alternative media for learning.The application of technology integration in mathematics learning has the principle of optimizing the usefulness of technology in the mathematics learning process in mastering mathematics and increasing conceptual understanding and develop math skills. Technological adaptations can be applied to mathematics learning by utilizing platform or applications that can support the online learning process in the form of Edmodo or Microsoft Teams-based learning